Structural Characterization and Anticoagulant Activity of a 3-O-Methylated Heteroglycan From Fruiting Bodies of Pleurotus placentodes - Yin, Zhen-Hua; Liu, Xiao-Peng; Wang, Jin-Mei; Xi, Xue-Feng; Zhang, Yan; Zhao, Rui-Lin; Kang, Wen-Yi (Frontiers in Chemistry, 2022)
Pleurotus placentodes, a fungus, belongs to the Pleurotaceae family. The aim of the present study was to characterize the structure of a novel polysaccharide from fruiting bodies of P. placentodes (PPp-W) and evaluate its anticoagulant activity in vitro. The high-performance liquid chromatography and GC–MS analysis indicated that PPp-W with a molecular weight of 27.4 kDa was mainly composed of mannose (17.56%), glucose (6.37%), galactose (44.89%), and fucose (1.22%) with a certain amount of 3-O-methyled galactose. SEM, XRD, and AFM combined with Congo red test revealed that PPp-W was an irregular curly sheet with triple-helix conformation. The FT-IR, methylation, and nuclear magnetic resonance analysis indicated that PPp-W contained→6)-α-D-Galp-(1→, →6)-3-O-Me-α-D-Galp-(1→and →2, 6)-α-D-Galp-(1→ as main chain, partially substituted at O-2 and O-6 by non-reducing ends of β-D-Manp-(1→ and β-L-Fucp-(1→ with a small amount of α-1,3-linked-Glcp in backbone. PPp-W could significantly prolong APTT (12.9 ± 0.42 s, p < 0.001) and thrombin time (39.9 ± 0.28 s, p < 0.01) compared with the control group (11.45 ± 0.071 s and 38.05 ± 0.21 s), which showed that PPp-W had anticoagulant activity. These studies suggested that PPp-W was a 3-O-methylated heteroglycan and might be suitable for functional foods and natural drugs as an anticoagulant ingredient, which provided a basis for the application of polysaccharides from P. placentodes.